Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/bf03175204
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing crop growth, nutrients availability, economics and beneficial rhizosphere microflora through organic and biofertilizers

Abstract: Field experiment was conducted on fodder maize to explore the potential of integrated use of chemical, organic and biofertilizers for improving maize growth, beneficial microflora in the rhizosphere and the economic returns. The treatments were designed to make comparison of NPK fertilizer with different combinations of half dose of NP with organic and biofertilizers viz. biological potassium fertilizer (BPF), Biopower, effective microorganisms (EM) and green force compost (GFC). Data reflected maximum crop gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(66 citation statements)
references
References 18 publications
6
59
0
1
Order By: Relevance
“…Compared to CaMgP the further amendment with organic fertilizer did not change soil DTPA-extractable metals (Table 5). Nevertheless, the application of organic fertilizer could improve soil structure, conserve the nutrients in soil, and enhance the soil microbial biomass, activity and diversity, which in turn improved the crop growth and restrained metal toxicity (Goyal et al, 1999;Jilani et al, 2007;Zhang et al, 2012).…”
Section: Soil Property Initial Soilsmentioning
confidence: 99%
“…Compared to CaMgP the further amendment with organic fertilizer did not change soil DTPA-extractable metals (Table 5). Nevertheless, the application of organic fertilizer could improve soil structure, conserve the nutrients in soil, and enhance the soil microbial biomass, activity and diversity, which in turn improved the crop growth and restrained metal toxicity (Goyal et al, 1999;Jilani et al, 2007;Zhang et al, 2012).…”
Section: Soil Property Initial Soilsmentioning
confidence: 99%
“…It has been proven that these bacteria increase the qualitative/quantitative yields of most crops through biological fixation of nitrogen, biological control of plant pathogens (Saravanakumar et al, 2007;Dey et al, 2004), vitamin production, increased iron absorption by siderophore secretion (Shaharoona et al, 2008;Braud et al, 2009) and production of the plant hormones cytokinin, auxin and gibberellin (Dey et al, 2004), decreasing levels of ethylene by production of Acc deaminase (Shaharoona et al, 2008) and increasing phosphorus solubility. Previous studies have shown that co-inoculation of phosphate-solubilizing bacteria (PSB) with other growth-promoting rhizobacteria decreased phosphate fertilizer consumption by 50% without a significant reduction in grain yield (Jilani et al, 2007;Yazdani et al, 2009). The ability of Pseudomonas to solubilize P affects the yield, growth parameters, and P uptake of faba beans (Crowley, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Intensive nutrient uptake by the crops and insufficient nutrients input through fertilizers are among the major constraints related to declining crop yields in Pothwar region (Jilani et al, 2007). The soil with adequate fertility can help crop plants better utilize the available soil water.…”
Section: Resultsmentioning
confidence: 99%
“…Plant nutrients N, P, Zn and B were applied as improved fertilizer application treatment because these nutrients showed alarming deficiency in experimental areas in soil analysis ( Table 1). The term improved /balanced fertilizer application in this study means application of deficient nutrients and other fertilizers at recommended rates based on several studies carried out in rainfed area (Shafiq et al, 2003;Jilani et al, 2007;Shaheen et al, 2010). There were four treatments as described below:…”
Section: Experimental Design and Treatmentsmentioning
confidence: 99%